Psychic Empire - Reilly, Cate I. (Columbia University Press, 2024)
Cate I. Reilly argues that modernist texts can be understood as critically responding to objective scientific models of the psyche, not simply illustrating their findings.
Description based on publisher supplied metadata and other sources
Keywords: Psychiatry in literature; Modernism (Literature)